Formulation and evaluation of gastro retentive floating tablets of atorvastatin calcium - Nansri Saha; Soumik Ghosh; Pawan Kumar; Satyabrata Bhanja; Sarita Tiwari (International Journal of Pharmacy and Analytical Research, 2022)
Atorvastatin calcium is a HMG-CoA reductase inhibitor used in the treatment of hyperlipidaemia. Oral bioavailability of atorvastatin calcium is less than 12%. It also undergoes high first pass metabolism. It is absorbed more in the upper part of the GIT.10 So oral absorption of atorvastatin can be increased by increasing gastric retention time of the drug. Thus it is decided to prolong the gastric residence time in terms of making floating gastro retentive drug delivery system to increase drug absorption and hence bioavailability. In this study Atorvastatin calcium floating tablets were prepared by using two different techniques like Effervescent floating tablets and Non Effervescent floating tablets using Ethyl cellulose, Karaya gum and HPMC K4 M as polymers and gas generating agents like sodium bicarbonate and citric acid and polypropylene foam powder a s a selling agent in non effervescent floating tablets. The tablets prepared by direct compression technique were evaluated in terms of their pre-compression parameters and post compression characteristics such as physical characteristics, total buoyancy, buoyancy lag time, swelling index and in vitro release. The best formulation showed no significant change in physical appearance, drug content, total buoyancy time, buoyancy lag time or in vitro release after storage at 40˚C /75% RH for three months. The in vitro release studies confirmed that the formulation (F24) containing 90 mg of karaya gum showed sustained drug release (98.81±0.32%) for 12 h and remained buoyant for more than 12 h by using Effervescent floating technique.